Annual Report on Exchange Arrangements and Exchange Restrictions 2016. (Annual Report on Exchange Arrangements and Exchange Restrictions, 2016)
The AREAER provides a description of the foreign exchange arrangements, exchange and trade systems, and capital controls of all IMF Member countries.